Sexuality in China : histories of power & pleasure - Chiang, Howard, 1983- (University of Washington Press, 2018)
What was sex like in China, from imperial times through the post-Mao era? The answer depends, of course, on who was having sex, where they were located in time and place, and what kind of familial, social, and political structures they participated in. This collection offers a variety of perspectives by addressing diverse topics such as polygamy, pornography, free love, eugenics, sexology, crimes of passion, homosexuality, intersexuality, transsexuality, masculine anxiety, sex work, and HIV/AIDS. Following a loose chronological sequence, the chapters examine revealing historical moments in which human desire and power dynamics came into play. Collectively, the contributors undertake a necessary historiographic intervention by reconsidering Western categorizations and exploring Chinese understandings of sexuality and erotic orientation.
Keywords: Sex -- China -- History.; Sex customs -- China -- History.; Sexualité -- Chine -- Histoire.; Vie sexuelle -- Chine -- Histoire.; POLITICAL SCIENCE / Public Policy / Cultural Policy.; SOCIAL SCIENCE / Anthropology / Cultural.; SOCIAL SCIENCE / Popular Culture.; HISTORY / Asia / China; Sex; Sex customs; China; Sexualverhalten; History; Aufsatzsammlung.